Management of water resources in the Wae Rupa Watershed in the Perception of the Community of Hukurila Village, Ambon City - Tella, Dwi H N; Latuamury, Bokiraiya; Sahureka, Mersiana (Pattimura University Ambon Maluku Indonesia, 2024)
Community-based water resources management is an approach that accommodates the active role of communities in protecting and conserving water resources. This research aims to analyze the correlation between the socio-economic characteristics of the community and community-based water resource management in Hukurila village, Ambon City. The data collection method uses interviews and field observations with data analysis using Rank-Spearman correlation to analyze the correlation between research parameters. This means that every form of natural resource utilization is carried out by considering watershed sustainability aspects. The analysis results of the community perceptions (knowledge and attitudes) assessment regarding community-based water resources management show that the level of community knowledge is in the high category, and the attitude assessment is in the medium category. The results of the Spearman Rank analysis between the level of knowledge and attitudes related to water resources management obtained a Spearman coefficient of 0.446 with a significance of 0.001 at the 99% confidence level. In comparison, the active attitude of the community with community-based watershed management obtained a Spearman coefficient of 0.337 with a significance of 0.017 at the 95% confidence level. Community perception, which includes community knowledge and attitudes, has a positive and significant relationship with sustainable and sustainable watershed management.